2021
DOI: 10.3390/app11114939
|View full text |Cite
|
Sign up to set email alerts
|

A Traceable and Verifiable Tobacco Products Logistics System with GPS and RFID Technologies

Abstract: Tobacco products are an addictive commodity. According to the World Health Organization’s (WHO) latest statistics data, tobacco kills more than eight million people each year. In 2003, the WHO proposed the Framework Convention on Tobacco Control (FCTC) to provide an effective framework for the control of tobacco products to governments around the world. In the field of tobacco products, the hardest problem is how to prevent counterfeit tobacco products and smuggling. To solve the problems, we proposed a blockc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…This also confirms our hypothesis that the growers' attitude positively influences their intention toward a traceable mango value chain. These findings are consistent with the findings of [25]. Similarly, [26] indicated that attitude is fundamental in influencing intentions to perform different safe food-handling behaviors.…”
Section: Resultssupporting
confidence: 89%
“…This also confirms our hypothesis that the growers' attitude positively influences their intention toward a traceable mango value chain. These findings are consistent with the findings of [25]. Similarly, [26] indicated that attitude is fundamental in influencing intentions to perform different safe food-handling behaviors.…”
Section: Resultssupporting
confidence: 89%
“…It adopts a modular universal framework, unique identity management, access control functions, and channels to transfer data. Those features are suitable for various industrial applications, such as supply chain tracking [58,59], financial management [60], insurance financial [61], healthcare records [62,63], etc. The advantages of the blockchain's characteristics are listed as follows:…”
Section: Blockchain-based Smart Contractmentioning
confidence: 99%
“…If the suspect finds abnormal marks on the appearance of the luggage when picking up the luggage, the suspects will give up the luggage in order to escape the guilt, and the customs staff will not be able to catch the suspect in time. Although the contraband can be detected, catch the suspect will be not in time [ [12] , [13] , [14] ]. For RFID tracking system, luggage tags contain sensitive information such as the passenger's name and destination, which could be stolen.…”
Section: Introductionmentioning
confidence: 99%